Spillovers through Multimarket Firms: The Uniform Product Replacement Channel - Hyun, Jay; Kim, Ryan (The Review of Economics and Statistics, 2026)
Abstract We study how regional housing market disruptions spill over across US local markets through multimarket firm networks. Using granular barcode-level data linked to producer information, we exploit variation in firms’ exposure to local house price declines. A firm’s local sales respond more strongly to indirect housing price declines in its other markets than to direct local declines. The barcode-level data reveal a novel uniform product replacement mechanism: Firms respond to adverse shocks by replacing higher-value products with lower-value alternatives uniformly across all markets. This propagates regional demand shocks through the supply side, with new implications for regional economics.